NATURE OF THE LABILE IMMUNOGENIC SUBSTANCE IN THE PARTICULATE FRACTION ISOLATED FROM MYCOBACTERIUM TUBERCULOSIS - Youmans, Anne S. (1964)
Youmans, Anne S. (Northwestern University Medical School, Chicago, Ill.), and Guy P. Youmans. Nature of the labile immunogenic substance in the particulate fraction isolated from Mycobacterium tuberculosis. J. Bacteriol. 88:1030–1037. 1964.—Deoxyribonuclease had no effect on the immunogenic activity of the labile particulate fraction isolated from ruptured viable cells of the H37Ra strain of Mycobacterium tuberculosis, but decreased the ropiness of the ruptured cellular mass. Ribonuclease, in a high concentration, decreased the immunogenic activity slightly. Addition of yeast ribonucleic acid to particulate fraction incubated at 37 C prevented the decrease in immunogenic activity which normally occurs at this temperature, suggesting that endogenous ribonuclease may be involved in the reduction of activity. Differential centrifugation by the use of Brodie's (1962) method showed that the particles which sedimented at 56,550 × g were immunogenically active. Experiments were done to determine whether the integrity of the structure of the particle was necessary for immunogenic activity. It was found that sonic oscillation, freezing and thawing several times, the addition of surface-active agents (sodium lauryl sulfate or deoxycholate), and preparation of the particulate fraction in hypotonic solutions either decreased or destroyed immunogenic activity. This strengthens the evidence that a structural unit is necessary for activity. In addition, both a waxy sediment and the smallest particles which sedimented only at 144,000 × g were highly immunogenic if incorporated into Freund's incomplete adjuvant. In the absence of adjuvant, neither produced any immunity.